Prevalence of childhood overweight and obesity in Malaysia: a systematic review and meta-analysis - Ker Yang Chua; Ker Yung Chua; Karuthan Chinna; Chooi Ling Lim; Maheeka Seneviwickrama (Clinical and Experimental Pediatrics)
The incidence of childhood obesity is increasing worldwide. National surveys in Malaysia have shown similar trends. This review aimed to increase our understanding of the prevalence and associated factors of childhood overweight, obesity, and excess weight in Malaysia. A systematic review and meta-analysis were conducted of studies reporting the prevalence of overweight and obesity in Malaysian children aged <18 years. Systematic searches were conducted in October 2023 and repeated in March 2024 of the PubMed, Scopus, and Web of Science databases. The grey literature was also included. Study selection, data extraction, and quality assessments were conducted by paired independent researchers. A meta-analysis of prevalence and 95% confidence interval (CI) using a random-effects model and heterogeneity (I2) was calculated. Publication bias was investigated using Egger’s test. This review included 33 studies (N=273,710) conducted between 1996 and 2022. Overall, the childhood overweight, obesity and excess weight prevalence was 13.9% (95% CI, 13.0%–14.8%), 11.8% (95% CI, 10.9%–12.8%), and 24.0% (95% CI, 22.3%–25.7%), respectively. Boys had a significantly higher proportion of obesity (12.5% [95% CI, 11.1%–14.1%] vs. 9.1% [95% CI, 8.1%–10.1%]) and excess weight (25.7% [95% CI, 23.5%–28.1%] vs. 20.7% [95% CI, 18.8%–22.8%]) than girls. Sarawak natives had a higher prevalence of obesity (17.7% [95% CI, 16.0%–19.5%]). Annually, the obesity prevalence increased by 0.3% (95% CI, 0.1%–0.6%; P=0.006) and excess weight prevalence increased by 0.6% (95% CI, 0.3%–1.0%; P=0.002). Heterogeneity was high (I2>90%), and publication bias was possible (P<0.001). Variability was not significantly affected by the critical appraisal score or sample size. In conclusion, the prevalence of childhood overweight, obesity, and excess weight in Malaysia doubled over 26 years. Future studies of the prevalence of childhood excess weight should follow a standardized reference for body mass index by age to ease interstudy comparisons.